Digital Curation and the Strengthening of Educational Literacy (Systematic Literature Review Study) - Nasyor, Hilmy Shalahudin; Rusydiyah, Evi Fatimatur (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
In the expansion of digital information, it is not enough for people to simply search for data. This study intends to investigate the trends, techniques, and results of digital curation and educational literacy enhancement by using SLR approach and PRISMA 2020 protocol. A total of 30 articles were obtained from the database of Scopus, spanning 2015 to 2026. Thematic analysis was used to identify the patterns and themes that were visible in varied literature. The results show that the research increased after 2020, due to the digital acceleration caused by the pandemic. Four key themes surfaced: digital curation fosters information and digital literacy (36.7%); it fosters critical thinking and evidence-based decision-making (26.37%); Digital curation is the administration of media and educational materials (16.7%); it also promotes educators' professional development (20.0%). Developmental and conceptual approaches were the most commonly used techniques (26.7% of papers). Four benefits of digital curation on educational literacy have been noted in a number of articles: an increase in digital and information literacy skills; the encouragement of critical thinking and evidence-based decision making; support for teachers' professional development; and assistance in managing digital media and learning resources